Development of a range of plausible future land use, land management and growing season changes - Holman, Ian P.; Hess, Tim M. (Cranfield University, 2014)
This report is part of the "Land use, climate change & water availability (Phase 2a)" project which was commissioned and funded by the Department for Environment, Food and Rural Affairs (Defra). Based on a review of the literature, it describes plausible characteristics of future land use and management changes (induced by climate or social change by the 2050s) that are likely to influence water availability.
Keywords: climate change, water, landuse, land use